Unveiling island tourism in Cape Verde through online reviews - Oliveira, C. (2021)
This paper is focused on research addressing a large quantity of data extracted from online reviews written by tourists visiting islands. These were extracted from Trip Advisor regarding island tourist destinations since there is a gap in the scientific literature using this approach on island tourism. The Islands of the Sun, Boa Vista and Sal, of Cape Verde, a Small Island Developing State (SIDS), were the targets of this investigation. After applying text mining to a large dataset, results are discussed, including from the perspectives of hotels, restaurants, and tourist attractions. For example, the beach is the main tourist attraction in both islands, but whereas in Boa Vista, tours on quad bikes constitute a major tourist activity, its equivalent in Sal is actually diving. The location of hotels near the beach is a big plus for tourists who also emphasize their human interaction with staff members in both hotels and restaurants.